O-072 Can preimplantation genetic testing for monogenic conditions represent an indication for DuoStim? A multicenter case series. (30th June 2022) - Trabucco, E; Vaiarelli, A; Cimadomo, D; Innocenti, F; Alfano, S; Malagisi, F; Della Ragione, A; Benini, F; Livi, C; Colamaria, S; Argento, C; Bruno, G; et al.
Abstract: Study question: Is double stimulation in the same ovarian cycle (DuoStim) a valuable strategy to improve the chance of success in couples carrier of monogenic conditions? Summary answer: DuoStim is advantageous in patients indicated for preimplantation genetic testing for monogenic diseases and aneuploidy testing (PGT-M/-A) and obtaining ≤5 blastocysts after the I-stimulation. What is known already: PGT-M is a well-established strategy to identify unaffected blastocysts in a cohort of embryos produced from couples carrier of single gene disorders. When PGT-M is conducted in poor prognosis and/or advanced maternal age (POR/AMA) patients, also aneuploidy-testing among unaffected blastocysts is suggested on a single biopsy. The Poseidon group stated that retrieving an adequate number of oocytes to produce ≥1 euploid blastocyst should be considered the main goal of controlled-ovarian-stimulation (COS). This task is even more complex when PGT-M is required in POR/AMA patients. Therefore, lately we started suggesting DuoStim to these couples to maximize their chance of success. Study design, size, duration: Multicenter case series (2016-2021). Comprehensive description of IVF outcomes derived from DuoStim application in POR/AMA patients undergoing PGT-M. Aneuploidy-testing was also conducted on unaffected blastocysts. All results were compared between the two stimulations in the same ovarian cycle, and we reported the contribution of II-stimulations to higher chances of success. Participants/materials, setting, methods: GnRH-antagonist COS was performed with recombinant-gonadotrophins and agonist-trigger. Based on the expected risk each embryo would be affected-aneuploid, DuoStim was suggested to all patients obtaining ≤5 blastocysts (day5-7 from I-retrieval). 61 patients accepted and underwent II-stimulations with the same protocol. Only ICSI, trophectoderm-biopsy, qPCR, and vitrified-warmed unaffected-euploid single-blastocyst-transfer(s) were conducted. Main results and the role of chance: 90 patients (36.7±3.7yr) indicated to PGT-M/-A and obtaining ≤5 blastocysts after I-stimulations were suggested starting a II-stimulation in the same ovarian cycle. Among them, 61 accepted (67%). 7.2±4.4 and 7.4±4.2 cumulus-oocyte-complexes were retrieved after I- and II-stimulations, respectively (p = 0.7). 5.1±3.0 and 5.8±3.4 were metaphase-II oocytes (p = 0.2), resulting in 75±21% and 77±25% maturation-rates (p = 0.6). 3.6±2.1 and 4.6±2.9 2PN-zygotes were obtained (p = 0.04), resulting in 75±27% and 81±20% fertilization-rates (p = 0.19). 1.6±1.3 and 2.2±1.8 blastocysts were obtained (p = 0.04), resulting in 43±32% and 46±32% blastulation-rates (p = 0.6). Lastly, 0.5±0.7 and 0.7±1.0 blastocysts were diagnosed unaffected-euploid (p = 0.3), resulting in 35±40% and 30±36% transferable blastocyst rates per biopsied embryo, respectively (p = 0.53), and identical 10±16% transferable blastocyst rates per metaphase-II oocyte in both groups (p = 0.9). 23 (38%) and 24 (39%) patients obtained ≥1 transferable blastocyst after the I- and II-simulation, respectively. Overall, 36 (59%) patients obtained ≥1 transferable blastocyst thanks to DuoStim. To date, 57 (93%) cycles were concluded, and the cumulative live birth rate (CLBR) was 37% (N = 21/57). The patients with a LB have 1.7 surplus transferable blastocysts, and 3 patients already delivered 2 singleton healthy-LBs. The CLBR among patients undergoing the conventional strategy was 21%, no surplus transferable blastocyst is available, and no patient delivered >1 LB. Limitations, reasons for caution: Observational case series based on real-life data. Of note, the adoption of DuoStim (or any other oocyte/embryo accumulation strategy) in PGT-M/-A is valuable also to amortize the costs of PGT-M set-up and genetic testing through a larger number of blastocysts. In this context, cost-effectiveness analyses in different settings are desirable. Wider implications of the findings: DuoStim is a fully-personalized strategy advisable any time lower chance of success and higher treatment costs could be balanced by a larger number of blastocysts produced in a short time-frame. Adopting GnRH-antagonist protocols in these patients allows to suggest DuoStim even in progress, based on the embryological outcomes after I-stimulations. Trial registration number: Not applicable